Febrile seizures: an update. Issue 8 (21st July 2004) - Waruiru, C; Appleton, R
Abstract : This review focuses on the latest knowledge and understanding of febrile seizures and outlines the more important issues in the management of children who present with an apparent "febrile seizure". It is not the remit of this paper to discuss the detailed management of febrile seizures. Throughout this review, the words "partial" and "focal" will be used interchangeably and the term "febrile seizure" (FS) will be used, reflecting the proposed changes in the terminology of seizures and epilepsies.1